Advantages of adjuvant chemotherapy for patients with triple-negative breast cancer at Stage II: usefulness of prognostic markers E-cadherin and Ki67 - Kashiwagi, Shinichiro (BioMed Central, 2011)
INTRODUCTION: Triple-negative breast cancer (TNBC), which is characterized by negativity for estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 (HER2), is a high risk breast cancer that lacks specific targets for treatment selection. Chemotherapy is, therefore, the primary systemic modality used in the treatment of this disease, but reliable parameters to predict the chemosensitivity of TNBC have not been clinically available. METHODS: A total of 190 TNBC patients who had undergone a curative resection of a primary breast cancer were enrolled. The adjuvant chemotherapy was performed for 138 (73%) of 190 TNBC cases; 60 cases had an anthracyclin-based regimen and 78 a 5-fluorouracil-based regimen. The prognostic value of E-cadherin, Ki67 and p53 expression in the outcome of TNBC patients with adjuvant chemotherapy was evaluated by immunohistochemistry. RESULTS: The adjuvant therapy group, especially those with Stage II TNBC, had a more favorable prognosis than the surgery only group (P = 0.0043), while there was no significant difference in prognosis between the anthracyclin-based regimen and 5-fluorouracil-based regimen. Patients with E-cadherin-negative and Ki67-positive expression showed significantly worse overall survival time than those with either E-cadherin-positive or Ki67-negative expression (P < 0.001). Multivariate analysis showed that the combination of E-cadherin-negative and Ki67-positive expression was strongly predictive of poor overall survival (P = 0.004) in TNBC patients receiving adjuvant chemotherapy. In contrast, p53 status was not a specific prognostic factor. CONCLUSIONS: Adjuvant therapy is beneficial for Stage II TNBC patients. The combination of E-cadherin and Ki67 status might be a useful prognostic marker indicating the need for adjuvant chemotherapy in Stage II TNBC patients.